Effect of physical activation/surface functional groups on wettability and electrochemical performance of carbon/activated carbon aerogels based electrode materials for electrochemical capacitors. (7th May 2020) - Abbas, Qaisar; Mirzaeian, Mojtaba; Ogwu, Abraham A.; Mazur, Michal; Gibson, Des
Abstract: Polymeric carbon/activated carbon aerogels were synthesized through sol-gel polycondensation reaction followed by the carbonization at 800 °C under Argon (Ar) atmosphere and subsequent physical activation under CO2 environment at different temperatures with different degrees of burn-off. Significant increase in BET specific surface area (SSA) from 537 to 1775 m 2 g − 1 and pore volume from 0.24 to 0.94 cm 3 g − 1 was observed after physical activation while the pore size remained constant (around 2 nm). Morphological characterization of the carbon and activated carbons was conducted using X-ray diffraction (XRD) and Raman spectroscopy. Fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were used to investigate the effect of thermal treatment (surface cleaning) on the chemical composition of carbon samples. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to analyse the capacitive and resistive behaviour of non-activated/activated/and surface cleaned activated carbons employed as electroactive material in a two electrode symmetrical electrochemical capacitor (EC) cell with 6 M KOH solution used as the electrolyte. CV measurements showed improved specific capacitance (SC) of 197 Fg − 1 for activated carbon as compared to the SC of 136 Fg − 1 when non-activated carbon was used as electroactive material at a scan rate of 5 mVs −1 . Reduction in SC from 197 Fg − 1 to 163 Fg − 1 was witnessed after surface cleaning at elevated temperatures due to the reduction of surface oxygen function groups. The result of EIS measurements showed low internal resistance for all carbon samples indicating that the polymeric carbons possess a highly conductive three dimensional crosslinked structure. Because of their preferred properties such as controlled porosity, exceptionally high specific surface area, high conductivity and desirable capacitive behaviour, these materials have shown potential to be adopted as electrode materials in electrochemical capacitors. Graphical abstract: Highlights: Polymeric carbon/activated carbon aerogels were synthesized through sol-gel polycondensation reaction. Significant increase in BET SSA from 537 to 1775 m 2 g −1 was observed after physical activation using CO2 . Improved SC of 197 Fg −1 was achieved after activation as compare to 136 Fg −1 for non-activated carbon aerogels. Significant decrease in contact angle was observed when carbon substrate was substituted with activated carbon.